SYSTEMIC DYNAMICS OF GLOBAL DRUG TRAFFICKING AND THE SECURITY POSITIONING OF THE SOUTH CAUCASUS (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
This article analyzes the systemic dynamics of global drug trafficking, focusing on its spatial structure, development patterns, and security implications. The study examines the interconnections between production, transit, and consumption zones within the context of the formation and transformation of global supply networks. Particular attention is paid to geopolitical, socioeconomic, and institutional factors that shape the spatial dynamics and adaptive capacity of drug trafficking networks. The research applies comparative analysis, geographic mapping, and statistical data processing to identify high-risk regions and the main trafficking routes. A separate analytical section explores the security positioning of the South Caucasus as a crossroads transit zone within the global drug trafficking system, where multiple regional routes and security challenges intersect. The findings indicate that drug trafficking represents a multidimensional security threat affecting state stability, border security, and regional cooperation. The article contributes to the theoretical and applied study of drug trafficking and provides a conceptual basis for developing effective prevention and counteraction strategies in the South Caucasus.
Keywords: narcotrafficking; security threats; transit regions; South Caucasus